2017
DOI: 10.7717/peerj.3681
|View full text |Cite
|
Sign up to set email alerts
|

Selected nutritional habits of teenagers associated with overweight and obesity

Abstract: IntroductionA balanced diet is at the heart of healthy growth and development of children and youth, whereas inappropriate eating habits considerably influence the incidence of disorders connected with nutrition, including overweight and obesity. This paper aims at studying nutritional factors of 18-year-old secondary school youth in the urban environment and their effect on the incidence of overweight and obesity.Materials and methodsThe survey was conducted among 1,999 secondary school students chosen at ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 36 publications
2
45
0
3
Order By: Relevance
“…In the present study, 87.7% of students consumed fast food at least four times/day and the consumers were not more obese than their counterparts. A previous study ( 27 ) found that 84.1% of students consumed fast food regardless of their nutritional status and in accordance with the current observation. The previous study ( 27 ) reported no significant differences in BMI between fast food consumers and those who did not consume the food, which is in line with the current data.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, 87.7% of students consumed fast food at least four times/day and the consumers were not more obese than their counterparts. A previous study ( 27 ) found that 84.1% of students consumed fast food regardless of their nutritional status and in accordance with the current observation. The previous study ( 27 ) reported no significant differences in BMI between fast food consumers and those who did not consume the food, which is in line with the current data.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, awareness in maintain healthy lifestyle should begin from younger age to prevent obesity and its related comorbidities. A survey of nutritional habits in teenagers reported that eating errors (i.e., irregular eating, skipping breakfast) were more frequently observed in overweight and obese students as compared to the normal weight ones, and emphasized the importance of conveying the knowledge on the causes of overweight and obesity and the rules of healthy dieting (Zalewska & Maciorkowska, 2017).…”
Section: Urbanmentioning
confidence: 99%
“…We have found that eating breakfast less frequently increases the risk of fatty liver in children and adolescents. One study have found that skipping breakfast can cause overweight and obesity [31] . This may be the reason why these students are prone to fatty liver.…”
Section: Discussionmentioning
confidence: 99%